Faktor-Faktor yang Berhubungan Dengan Motivasi Belajar Mahasiswa Semester VI di Program Studi DIII Kebidanan STIKes Fort De Kock Bukittinggi Tahun 2013 - ., Ermiza (Jurnal Martenity and Neonatal, 2017)
Quality is strongly influenced by the educational institution for the education system inputs such as students, faculty and infrastructure facilities supporting the teaching and learning process. These three factors are interdependent and influence in creating a successful learning process . Educational problems often faced by students include lecture schedule is not fixed , often have difficulty adjusting to the course , the lecturers , the order must be obeyed , campus environment , the burden of higher education costs . That difficulties in the face of conflict in motivating them to continue zealous in following the lecture . The purpose of this study was to determine the " Factors Associated with Student Learning Motivation VI Semester " Program Diploma in Midwifery STIKes Fort De Kock Bukittinggi in 2013 ''. This type of research is a descriptive study with cross sectional approach Analytics , the number of samples taken from the entire population ( total sampling ) as many as 130 respondents Diploma of Midwifery Students . Data were collected by distributing questionnaires in the form of a questionnaire given to respondents . Data were analyzed with univariate and bivariate techniques with Chi- Squer. The result showed that there is a relationship between the role of the Clinical Instructor ( CI ) Academic or Student Learning Motivation Lecturer with as many as 80 people ( 61.5 % ) stated that the role of the Clinical Instructor ( CI ) Academic or less better lecturers with P value 0.013 and OR 2.667 , as many as 82 people ( 63.1 % ) stated that the role of the Clinical Instructor (CI) Field well with a P value less than 0.000 and OR 5.786 , and as many as 73 people ( 56.2 % ) were assessed poor infrastructure components with P value of 0.000 and OR 6.491. Based on the results of research conducted at the drag can be concluded that the Student Motivation is influenced by the role of the Clinical Instructor (CI) Academic or Faculty, the role of the Clinical Instructor ( CI ) Field , and Infrastructure .